Primary mitochondrial disease in the US: Data from patients and physicians' perspective on health care delivery - Karaa, Amel; Goldstein, Amy; Balcells, Cristy; Mann, Kira; Stanley, Laura; Yeske, Philip E.; Parikh, Sumit (Data in brief, 2019)
This article presents data that examine the patient's perception of health care delivery for mitochondrial disease in the US. It also presents the opinions of mitochondrial disease expert physicians about creating a specialised network of clinics to oversee the care of patients with this disease within the US. Two separate electronic surveys were developed; one for mitochondrial disease patients and their families ascertaining their satisfaction with their current health care and the challenges they face. The other for the physicians group assessing the usefulness, feasibility and readiness to develop specialized care clinics for mitochondrial disease in the US. Survey responses and descriptive analysis are presented here. The data in this article is supplemental, and supports the information presented in the research article “Harmonizing care for rare diseases: How we developed the mitochondrial care network in the United States.” Karaa et al., 2019